Cα–H Oxidations of Amines to Amides: Expanding Mechanistic Understanding and Amine Scope through Catalyst Development - Legacy, Christopher J.; Emmert, Marion H. (Synlett, 2016)
This highlight provides a general overview of Cα–H oxidations of amines to form amides. Initial as well as recent examples are reviewed with a particular focus on existing challenges regarding substrate scope and reaction conditions. Finally, one very recently established catalyst system is described in detail which achieves the iron-catalyzed, Cα–H oxidation of amines under mild conditions.1 Introduction2 First C–H Oxygenations3 State of the Art: Oxidations of Primary, Secondary, Cyclic, Benzylic, and Aromatic Amines4 General Iron-Catalyzed C–H Oxidations under Mild Conditions5 Conclusions
Keywords: amides; catalysis; iron; oxidation; amines; biomimetic synthesis